The importance of offender motivation in violence reduction treatment - Berry, Lauren (2017)
The following academic thesis explores the links between offender motivation and violence reduction treatment for adult male offenders, with a focus on those with a mental illness. The thesis begins with a systematic review of the literature regarding the impact of motivation on interventions aimed at reducing violence and aggression. The majority of reviewed studies provided tentative support for the theory that individuals with higher levels of motivation stay in treatment longer and have better treatment gains regarding violence reduction. The following chapter includes an empirical study investigating the impact of Stage of Change, as measured by the Transtheoretical Model (Prochaska & DiClemente, 1982), on the outcome of treatment. The focus of this study was the Violent Offender Treatment Programme (VOTP), designed for mentally disordered offenders, and its application within a High Security and a Medium Security hospital. The programme itself was found to be effective in reducing violence outcomes, however there was little support for the Stages of Change model as a form of categorising those who were more likely to improve. Chapter 4 then presents a Case Study of an adult male offender, with a diagnosis of Delusional Disorder, in order to ascertain whether the VOTP could be adapted for individual use. Case study results were not clinically significant but are discussed in light of current research and forensic practice. A critical appraisal of the Violence Risk Scale (Wong & Gordon, 1998-2003) is then presented in Chapter 5, due to this being a primary risk assessment tool referred to throughout the doctoral works. The thesis concludes with a chapter summarising the key points and involving a reflective element by the author.